Protein-tyrosine Kinase p72syk Is Activated by Platelet Activating Factor in Platelets - Rezaul, Karim; Yanagi, Shigeru; Sada, Kiyonao; Taniguchi, Takanobu; Yamamura, Hirohei (Thrombosis and Haemostasis, 1994)
It has been demonstrated that activation of platelets by platelet-activating factor (PAF) results in a dramatic increase in tyrosine phosphorylation of several cellular proteins. We report here that p72syk is a potential candidate for the protein-tyrosine phosphorylation following PAF stimulation in porcine platelets. Immunoprecipitation kinase assay revealed that PAF stimulation resulted in a rapid activation of p72syk which peaked at 10 s. The level of activation was found to be dose dependent and could be completely inhibited by the PAF receptor antagonist, CV3988. Phosphorylation at the tyrosine residues of p72syk coincided with activation of yllsyk. Pretreatment of platelets with aspirin and apyrase did not affect PAF induced activation of p72syk.Furthermore, genistein, a potent protein-tyrosine-kinase inhibitor, diminished PAF-induced p72syk activation and Ca2+ mobilization as well as platelet aggregation. These results suggest that p72syk may play a critical role in PAF-induced aggregation, possibly through regulation of Ca2+ mobilization.